A Novel Mutation Glyl672→Arg in Type 2A and a Homozygous Mutation in Type 2B von Willebrand Disease - Hagiwara, Takeshi; Inaba, Hiroshi; Yoshida, Shinichi; Nagaizumi, Keiko; Arai, Morio; Hanabusa, Hideji; Fukutake, Katsuyuki (Thrombosis and Haemostasis, 1996)
Genetic materials from 16 unrelated Japanese patients with von Willebrand disease (vWD) were analyzed for mutations. Exon 28 of the von Willebrand factor (vWF) gene, where point mutations have been found most frequent, was screened by various restriction-enzyme analyses. Six patients were observed to have abnormal restriction patterns. By sequence analyses of the polymerase chain-reaction products, we identified a homozygous R1308C missense mutation in a patient with type 2B vWD; R1597W, R1597Q, G1609R and G1672R missense mutations in five patients with type 2A; and a G1659ter nonsense mutation in a patient with type 3 vWD. The G1672R was a novel missense mutation of the carboxyl-terminal end of the A2 domain. In addition, we detected an A/C polymorphism at nucleotide 4915 with HaeIII. There was no particular linkage disequilibrium of the A/C polymorphism, either with the G/A polymorphism at nucleotide 4391 detected with Hphl or with the C/T at 4891 detected with BstEll.